Autogenous bone and a bovine bone substitute for ridge preservation: preliminary clinical and histologic findings. (10th February 2016) - Schulz, MC; Kallweit, MB; Kallweit, S; Koch, R; Lauer, G; Mai, R; Hoffmann, T
Abstract: Background: Tooth extractions lead to morphological changes of the alveolar ridge. For oral rehabilitation sufficient bone volume of the alveolar ridge is required. This clinical study compared the ability of Bio‐Oss ® Collagen to autogenous bone to preserve bone volume after tooth extraction. Methods: A total of 17 patients with 20 extraction sites were examined. After extraction, 10 sockets were each filled with either autogenous bone or Bio‐Oss ® Collagen and covered with a resorbable membrane. The width of the alveolar ridge was measured postoperatively, and after 4 and 6 months respectively. Prior to implant insertion, a bone biopsy was taken from the grafted sites and evaluated histologically. Results: The width of the alveolar ridge in the Bio‐Oss ® Collagen group decreased about 5.33 ± 6.62% after 4 months and 9.45 ± 10.51% after 6 months. The reduction in the group augmented with autogenous bone was 14.31 ± 21.41% after 4 months and 19.17 ± 8.38% after 6 months. No statistically significant differences were observed. The histological examination showed comparable area fractions of total bone in both groups (Bio‐Oss ® Collagen: 59.99 ± 24.23%; autogenous bone: 61.55 ± 25.13%; p = 1.0). Conclusions: The present study demonstrated that autogenous bone and Bio‐Oss ® Collagen are suitable for ridge preservation. However, both techniques could not entirely prevent tissue volume loss.